Biology learning evaluation module development based on higher order thinking skills and local wisdom value - Najmiatul Fajar; Rima Dwi Suryani (STKIP Persada Khatulistiwa Sintang, 2023)
Modules are teaching materials that can support learning objectives. Modules can be studied independently so they are very helpful for lecturers in teaching. The purpose of this study was to determine the validity and practicality of the Biology Learning Evaluation Module based on Higher Order Thinking Skills (HOTS) and Local Wisdom values at IAIN Batusangkar. This research uses the type of R&D research with the 4D model (Define, Design, Develop, and Disseminate). The results of the due diligence were obtained from the results of expert validation with a score was 84.85% (very valid), while practical results obtained a score was 87.20% (very practical) from students and a score was 92.5% (very practical) from lecturers. So it can be concluded that the Biology Learning Evaluation Module based on Higher Order Thinking Skills and Local Wisdom Values is very feasible and very practical to use in the learning process of evaluating biology learning...